Analisis Deiksis Tuturan Movie Pendek Yang Berjudul Demi Nama Baik Kampus Pada Kanal Youtube Catatan Berkarakter Kemendikbud RI Tahun Rilis 2021 - Handayani, Auliya Tri; Pratiwi, Wienike Dinar; Setiawan, Hendra (Peneliti.net, 2023)
Sexual violence cases based on data collected on the kekerasan.kemenpppa.go.id website released the percentage of sexual violence cases that increased significantly from 2021-2023 with an increase in the occurrence of more than 50,000 cases. The increase in cases is not underestimated by the relevant government. One of the government's efforts to prevent cases of sexual violence is by forming a YouTube channel called Note Berkarakter Kemendikbud RI. In 2021, this YouTube channel released a short movie about a female student who experienced indications of sexual violence by her thesis supervisor, in which the movie presents a lot of characterizations, settings, and social conditions to get justice for the case that hit the female student. The relationship between the movie's speech and this study refers to references in the form of pronouns to references (other words) that describe pronouns, nouns, places, situations, to describe a person's position in the social environment. This research is a qualitative research that in the process of analyzing the data does not use numbers and is explained descriptively in the process of conclusion, is not generalization and does not consider significance. which focuses on the use of deiksis analysis theory that explains the characteristics of speech contests in a speech event that is used as an interpretation of the audience, there are four deiksis that can play a role in explaining the characteristics of short movie speech contests, namely persona deiksis, space deiksis, time deiksis, and social deiksis. Based on the results of the analysis of speech in the short movie, four types of deiksis were found and the form of deiksis, namely, persona deiksis consists of first-person persona deiksis, second-person persona deiksis, and third-person persona deiksis, then space deiksis consists of space deiksis with the use of demonstrative pronoun lexemes and the use of localative pronoun lexemes, time deiksis which describes time lexemes with respect to the rotation of the earth, Time deiksis that does not show calendar situations, and time deiksis using temporal conjunctions, and social deiksis that shows a description of a person's habits in describing one's profession, one's title and epithet towards someone.